The interspecific relationships between plants, cicadellids, and dryinids (Hemiptera: Cicadellidae - Hymenoptera: Dryinidae) - Giordano, Valeria (Acta entomologica slovenica (Ljubljana), 2002)
The relationships between 14 species of broadleaved trees, 29 species of cicadellids, 9 species of dryinids, and 1 species of a diapriid hyperparasitoid were examined in several areas of the western Piedmont (Northern Italy)
Keywords: insekti; listnato drevje; paraziti